Design of a Wastewater Collection Network for Kifl Hares Village along with cost estimate and assessment of potential location for a proposed Wastewater Treatment Plant - Hammad, Ghada; Jadallah, Rand (My University, 2018)
Water is the most important liquid for living on earth, as it is necessary for all the life of humans, animals and other living creatures. Water covers about seventy-one of the earth plant. Also is essential for industrial, agricultural and domestic usage. We use water daily in huge quantities and after use we dispose it of as a wastewater of about 60%-80% of water consumption. Wastewater generation have bad and destructive effects for the environment and the human if we don’t dispose them in a healthy and safe standards. The traditional way of the disposal of wastewater is the use of cesspit. It simply collects and stores the untreated wastewater, but this cesspit acts as a temporary solution and have a bad effect. So the best way to dispose wastewater of is by designing a wastewater collection network. The village of Kifl Hares was taken as a study area. It is in Salfit Governorate in the Northern West Bank. It does not have a wastewater collection network. And uses the cesspits (coated and not coated) which have a lot of problems including high cost for both the evacuation and maintenance, bad odors. And also the leak to groundwater may occur leading to enormous environmental issues such as harm diseases and pollution of water. So we need to design the wastewater collection network for Kifl Hares Village. To start designing specific information are needed such as contour map, roads, building, water recourses, water consumption rate per capita per day, population data now and population for the design period to evaluate the amount of wastewater generated for each manhole. When we construct it, we can make treatment for the wastewater and reuse in different type of ways, like irrigation which contributes in rationalizing water consumption. There are many conditions that have to be considered to select the location of treatment plant (TP) such as to be at the lowest point of the network, far from water resources, no Buildings, human, hospital or archaeological is there, as much as possible on a main road, away more than 150m of buildings and agricultures, Services be available, An area not vulnerable to natural disasters. The software that will be used in this project will be the Sewer CAD for designing the network, also GIS will be used.